Structural Model of Social, Physical and Mental Health and Physical Image Evaluation with Quality of Life: The Mediating Role of Limitations due to Chronic Pain of Elderly - Rezaei, Farideh; Bayazi , Mohammad Hosein; Rajaei , Alireza (Shahroud Journal of Medical Sciences, 2022)
Background: Chronic pain in the elderly leads to spending plenty of time and money, using health services, negative emotions, as well as reducing the quality of life and malfunctioning in the family. This study aimed to design a model of social, physical, and mental health and physical image evaluation with quality of life: the mediating role of limitations due to chronic pain of elderly in Tehran. Methods: This was a descriptive, analytical, retrospective study with a structural modeling approach that was performed on 270 elderly people (138 females and 132 males) between 60 and 70 years old living in Tehran. The sampling method was cluster random and convenience. To collect the data used Keyes social health questionnaire, Ware and Sherbourne health assessment questionnaire 36- SF, Body image evaluation of Godoosi, Manouchehri chronic pain limitation, and WHO elderly quality of life scales. Data analysis was performed using SPSS22 and Amos software through structural modeling using path analysis and confirmatory factor analysis. Results: The restriction variable due to chronic pain showed a negative relationship with physical and mental health (Pvalue<0.01, β =-0.734), evaluation of body image (Pvalue<0.01, β =-0.676), and social health (Pvalue<0.01, β =-0.691) in the quality of life of the elderly. A strong positive correlation (0.694 to 0.764) was obtained between the predictor variables (physical-mental health surveying, body image valuation, and social health) at a significance level of less than 0.01. Conclusions: The quality of life of the elderly was moderate and low; findings showed limitations caused by chronic pain are moderate the relationship of the quality of life in elderly with social, physical, mental health, and physical image evaluation. Keywords: Social health, Physical-mental health, Body image evaluation, Limitation due to chronic pain, Quality of life